Cardiorespiratory Fitness and All-Cause Mortality in Adults Diagnosed with Cancer Systematic Review and Meta-Analysis - Garcia-Hermoso, A (John Wiley and Sons Inc, 2021)
Introduction: The inverse association between cardiorespiratory fitness and all-cause mortality in apparently healthy populations has been previously reported; however, the existence of this association among adults diagnosed with cancer is unclear. Aim: To determine the association between cardiorespiratory fitness and all-cause mortality in adults diagnosed with cancer. Methods: Medline, Embase, and SPORTDiscus databases were searched. Eligible prospective cohort studies that examined the association of cardiorespiratory fitness with all-cause mortality in adults diagnosed with cancer were included. Hazard ratios (HRs) with associated 95% confidence intervals (CIs) were extracted from studies for all-cause mortality and pooled HRs were calculated using the random-effects inverse-variance model with the Hartung-Knapp-Sidik-Jonkman adjustment. Results: Data from 13 studies with 6,486 adults were included. Compared with lower levels of cardiorespiratory fitness, high levels were associated with a reduced risk of all-cause mortality among adults diagnosed with any cancer (HR = 0.52; 95% CI, 0.35–0.77), lung cancer (HR = 0.62; 95% CI, 0.46–0.83), and among those with cardiorespiratory fitness measurement via indirect calorimetry (HR = 0.47; 95% CI, 0.27–0.80). Pooled HRs for the reduction in all-cause mortality risk per 1-MET increase were also statistically significant (HR = 0.82; 95% CI, 0.69–0.99). Neither age at baseline nor the length of follow-up had a significant influence on the HR estimates for all-cause mortality risk. Conclusion: Cardiorespiratory fitness may confer an independent protective benefit against all-cause mortality in adults diagnosed with cancer. The use of cardiorespiratory fitness as a prognostic parameter might help determine risk for future adverse clinical events and optimize therapeutic management strategies to reduce long-term treatment-related effects in adults diagnosed with cancer. © 2021 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd